Multiway calibration strategy with chromatographic data exploiting the second order advantage for quantitation of three antidiabetic and three antihypertensive drugs in serum samples - Monzón, Celina María (2018)
Fil: Monzón, Celina M. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas Naturales y Agrimensura; Argentina.